Communication matters : materialist approaches to media, mobility and networks - Packer, Jeremy; Wiley, Stephen B. Crofts (Shaping inquiry in culture, communication and media studies, 2012)
Communication has often been understood as a realm of immaterial, insubstantial phenomena--images, messages, thoughts, languages, cultures, and ideologies--mediating our embodied experience of the concrete world. Communication Matters challenges this view, assembling leading scholars in the fields of Communication, Rhetoric, and English to focus on the materiality of communication. Building on the work of materialist theorists such as Gilles Deleuze, Michel Foucault, Friedrich Kittler, and Henri Lefebvre, the essays collected here examine the materiality of discourse itself and the constitutive force of communication in the production of the real. Communication Matters presents original work that rethinks communication as material and situates materialist approaches to communication within the broader "materiality turn" emerging in the humanities and social sciences. This collection will be of interest to researchers and postgraduate students in Media, Communication Studies, and Rhetoric